Evaluation of a Frequency-Domain Source Position Estimator for VBAP-Panned Recordings - Adami, Alexander; Herre, Jürgen (138th Audio Engineering Society Convention, AES 2015, 2015)
A frequency-domain source position estimator is presented which extracts the position of a VBAP-panned directional source by means of a direct-ambience signal decomposition. The directional signal components are used to derive an estimate of the panning gains which can be used to derive the estimated source position. We evaluated the mean estimated source positions as a function of the ideal source position as well as of different ambience energy levels using simulations. Additionally, we analyzed the influence of a second directional source to the estimated source positions.
herre_papers_spatial_audio_coding_and_3d_audio_coding